Mas-Related G Protein-Coupled Receptor-X2 (MRGPRX2) in Drug Hypersensitivity Reactions - Porebski, Grzegorz; Kwiecien, Kamila; Pawica, Magdalena; Kwitniewski, Mateusz (Frontiers in Immunology, 2018)
The human orthologue MRGPRX2 and the mice orthologue, Mrgprb2 are activated by basic secretagogues and neurokinins. A number of commonly used small-molecule drugs (e.g. neuromuscular blocking agents, fluoroquinolones, vancomycin) have been recently shown to activate these receptors under in vitro experimental conditions, what results in mast cell degranulation. The above drugs are also known to cause IgE-mediated anaphylactic reactions in allergic patients. The new findings on mechanisms of drug-induced mast cell degranulation may modify the current management of drug hypersensitivity reactions. Clinical interpretation of mild drug-provoked hypersensitivity reactions, interpretation of skin test with a drug of interest or further recommendations for patients suspected of drug allergy are likely to be reconsidered. In the paper we discussed future directions in research on identification and differentiation of MRGPRX2-mediated and IgE-dependent mast cell degranulation in patients presenting clinical features of drug-induced hypersensitivity reactions.